Herbert M. Caro ou o tradutor como lenda - Korfmann, Michael (Contingentia, 2008)
Fifteen years after his death in 1991 one can trace a certain tendency to turn the person and personality of Herbert Caro into a legendary figure where his work as a recognized translator mingles with episodes related to his passion for music as well as his specific kind of humour. It is therefore of no surprise that Caro himself turned into a literary character of the novel As Confissões de Lúcio by Brazilian writer Fernando Monteiro.